The Strengthening Religious Moderation for IPNU IPPNU Students through Interpretation Wasathiyah Efforts to Prevent Radicalism at Metro - Eka Prasetiawati; Muhammad Irsad; M. Rizal Ma'ruf Baharudin (Yayasan Payungi Smart Madani, 2024)
The phenomenon of intolerance that occurs among teenagers, especially in the school environment, outside school and even in universities. This country needs to be aware of the potential for radicalism and address how to overcome it. Today's young generation, especially Muslims who are still laymen, are easily influenced by Ustad's lectures on YouTube media (da'wah) which are quite viral and whose scientific knowledge is not yet clear. Therefore, this activity aims to provide theoretical and practical assistance to strengthen the understanding of moderation through Tafsir Wasathiyah for Metro City IPNU and IPPNU students. This activity adopts the Asset Based Community Development method, an approach that makes potential a strength in developing a community. Participants in this activity were 20 IPNU and IPPNU Metro city students. This activity was carried out in the Madrasah Aliyah Roudhotut Tholibin Metro Utara Hall. The results of this activity show that 1] IPNU and IPPNU MA Ma'arif Roudhotut Thalibin students are potential human resource assets for developing their abilities; 2] Strengthening the understanding of moderation through wasathiyah interpretation for Metro City IPNU and IPPNU students is very useful in order to avoid radicalism; 3] Helping students to have a spirit of nationalism through the practice of Aswaja practice because students at this age are very vulnerable to being infiltrated by intolerant ideas. Keywords: Strengthening Religious Moderation, Prevent Radicalism